Alert-based computerized decision support for high-risk hospitalized patients with atrial fibrillation not prescribed anticoagulation: a randomized, controlled trial (AF-ALERT). (22nd June 2019) - Piazza, Gregory; Hurwitz, Shelley; Galvin, Claire E; Harrigan, Lindsay; Baklla, Sofia; Hohlfelder, Benjamin; Carroll, Brett; Landman, Adam B; Emani, Srinivas; Goldhaber, Samuel Z
Abstract: Aims: Despite widely available risk stratification tools, safe and effective anticoagulant options, and guideline recommendations, anticoagulation for stroke prevention in atrial fibrillation (AF) is underprescribed. We created and evaluated an alert-based computerized decision support (CDS) strategy to increase anticoagulation prescription in hospitalized AF patients at high risk for stroke. Methods and results: We enrolled 458 patients (CHA2 DS2 -VASc score ≥1) with AF who were not prescribed anticoagulant therapy and were hospitalized at Brigham and Women's Hospital. Patients were randomly allocated, according to Attending Physician of record, to intervention (alert-based CDS) vs. control (no notification). The primary efficacy outcome was the frequency of anticoagulant prescription. The CDS tool assigned 248 patients to the alert group and 210 to the control group. Patients in the alert group were more likely to be prescribed anticoagulation during the hospitalization (25.8% vs. 9.5%, P < 0.0001), at discharge (23.8% vs. 12.9%, P = 0.003), and at 90 days (27.7% vs. 17.1%, P = 0.007). The alert reduced the odds of a composite outcome of death, myocardial infarction (MI), cerebrovascular event, and systemic embolic event at 90 days [11.3% vs. 21.9%, P = 0.002; odds ratio (OR) 0.45; 95% confidence interval (CI) 0.27–0.76]. The alert reduced the odds of MI at 90 days by 87% (1.2% vs. 8.6%, P = 0.0002; OR 0.13; 95% CI 0.04–0.45) and cerebrovascular events or systemic embolism at 90 days by 88% (0% vs. 2.4%, P = 0.02; OR 0.12; 95% CI 0.0–0.91). Conclusion: An alert-based CDS strategy increased anticoagulation in high-risk hospitalized AF patients and reduced major adverse cardiovascular events, including MI and stroke. ClinicalTrials.gov Identifier: NCT02339493.